Is there a single frontier in a single European banking market? - Jaap W. B. Bos; Heiko Schmiedel (European Central Bank (ECB), 2006)
This paper attempts to estimate comparable efficiency scores for European banks operating in the Single Market in the EU. Using a data set of more than 5000 large commercial banks from all major European banking markets over the period 1993-2004, the application of meta-frontiers enables us to assess the existence of a single and integrated European banking market. We find evidence in favor of a single European banking market characterized by cost and profit meta-frontiers. However, compared to the meta-frontier estimations, pooled frontier estimations tend to underestimate efficiency levels and correlate poorly with country-specific frontier efficiency ranks.
Keywords: G21; L11; L22; L23; 330; banking; meta-frontiers; stochastic frontiers; technology gap ratios; X-efficiency; Finanzmarkt; EU-Binnenmarkt; X-Effizienz; EU-Staaten